The Response of High School Students In Singkawang City Towards Physics Learning During Covid-19 Pandemic - Haris Rosdianto; Yoda Dafian; Riski Muliyani (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
This study aims to get an overview of the responses of high school students throughout Singkawang City about learning physics during the Covid-19 pandemic. This qualitative research uses a survey method. The subjects in this study were all state high school students in Singkawang City. The research sample was taken using the Convenience Sampling technique. Students' responses to learning physics during online learning are less liked by students because of limited internet signals and lack of guidance from teachers when learning online. This makes students less understand the physics material that is explained. The results of this study are, student responses in Very Good category by 2%, in Good category by 3%, while in Moderate category by 16%, and in Bad category by 79%.